2012
DOI: 10.1016/j.ridd.2012.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Allophonic mode of speech perception in Dutch children at risk for dyslexia: A longitudinal study

Abstract: There is ample evidence that individuals with dyslexia have a phonological deficit. A growing body of research also suggests that individuals with dyslexia have problems with categorical perception, as evidenced by weaker discrimination of between-category differences and better discrimination of within-category differences compared to average readers. Whether the categorical perception problems of individuals with dyslexia are a result of their reading problems or a cause has yet to be determined. Whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 64 publications
5
39
0
Order By: Relevance
“…The effect of school experience on allophonic sensitivity was confirmed in a longitudinal study with Dutch children at risk for dyslexia. These children exhibited a strong CP deficit when they were in kindergarten, characterized by both a weaker phonemic discrimination peak and a stronger allophonic peak; but this CP deficit was completely absent when they were in the first grade, after 6 months of formal reading instruction (Noordenbos, Segers, Serniclaes, Mitterer, & Verhoeven, 2012a). These findings might suggest that allophonic perception is not entirely specific to dyslexia and that it decreases with reading experience.…”
Section: Implications Of the Cp Deficit For Explaining Dyslexiamentioning
confidence: 83%
“…The effect of school experience on allophonic sensitivity was confirmed in a longitudinal study with Dutch children at risk for dyslexia. These children exhibited a strong CP deficit when they were in kindergarten, characterized by both a weaker phonemic discrimination peak and a stronger allophonic peak; but this CP deficit was completely absent when they were in the first grade, after 6 months of formal reading instruction (Noordenbos, Segers, Serniclaes, Mitterer, & Verhoeven, 2012a). These findings might suggest that allophonic perception is not entirely specific to dyslexia and that it decreases with reading experience.…”
Section: Implications Of the Cp Deficit For Explaining Dyslexiamentioning
confidence: 83%
“…Specifically, the 784 spectrotemporal sensitivity of the superior temporal gyrus (STG) has been linked to sensitivity to 785 phonetic features, such as voice onset time, place of articulation, and formant frequency (for a 786 review, see Leonard & Chang, 2014). Given functional and structural deviations in the STG 787 (Maisog, Einbinder, Flowers, Turkeltaub, & Eden, 2008;Paulesu et al, 2001;Simos et al, 2002;788 Steinbrink et al, 2008) and heightened sensitivity to phonetic features (e.g., Bogliotti et al, 789 2008;Noordenbos et al, 2013Noordenbos et al, , 2012aNoordenbos et al, , 2012bSerniclaes et al, 2004) …”
Section: Representations 765mentioning
confidence: 99%
“…Therefore, behavior 96 indicating greater subphonemic sensitivity would be consistent with the overspecification 97 hypothesis and at odds with underspecification. 98 less steep identification slopes, lower peak discrimination at the typical boundary, and additional 121 discrimination peaks at within-category stimulus pairs that often align with phonetic boundaries 122 between allophones (Noordenbos et al, 2012a(Noordenbos et al, , 2013Serniclaes et al, 2001Serniclaes et al, , 2004, suggesting 123 phonological representations organized allophonically rather than phonemically (Serniclaes, 124 2006). Although categorical perception tasks have proved fruitful in assessing underlying 125 phonological representations, they nevertheless require post-perceptual meta-linguistic 126 judgments, and so might not be sensitive to subtleties of online speech processing.…”
mentioning
confidence: 99%
“…This theory suggests that speech perception is not degraded in DD on an acoustic level, but instead, not adequately attuned to the phonetic contrasts present in the native language. This hypothesis has further been supported using behavioral and neuroimaging measures in children at risk for DD (Noordenbos, Segers, Serniclaes, Mitterer, & Verhoeven, 2012a, 2012b. With regard to speech production, it has been shown that both articulatory skills (Catts, 1986(Catts, , 1989 and oral motor skills are impaired in people with DD (Malek, Amiri, Hekmati, Pirzadeh, & Gholizadeh, 2013;Smith, Roberts, Lambrecht-Smith, Locke, & Bennett, 2006).…”
Section: A Phonological Processing Deficit In Ddmentioning
confidence: 85%